Pengaruh dosis bokashi pupuk Kambing terhadap tingkat serangan hama pada tanaman kacang hijau (Vigna radiata L.) - Nurlailah; Parari, Trisday Yiin; Wibawati, Zarima (Program Pascasarjana Universitas Papua, 2025)
One of the limiting factors in mung bean cultivation is the presence of pest attacks that can attack. Chemical pest control is dangerous for the environment and vegetation so it needs biological control. Based on the results of research, potassium nutrient content is able to maintain plant resistance to pest and disease attacks. The purpose of this study was to test the level of pest attacks on mung bean plants given various doses of goat waste bokashi. The research method used a single factor randomized block design with six treatment levels L0 = No bokashi treatment (Control), L1 = Treatment dose 2.4 kg (6 tons/ha), L2 = Treatment dose 4.8 kg (12 tons/ha), L3 = Treatment dose 7.2 kg (18 tons/ha), L4 = Treatment dose 9.6 kg (24 tons/ha), L5 = Treatment 12 kg (30 tons/ha). Observation variables were the number of perforated leaves, the number of torn leaves, the number of flowers, the number of flowers that successfully formed pods, the number of infected pods and productivity. Observation data were analyzed using analysis of variance (ANOVA) and further test LSD 0.05. The research results showed that 7.2 kg (18 tons/ha) of goat waste bokashi was the optimal dosage for increasing plant resistance to pest attacks and achieving optimal yield. The number of flowers formed and the number of flowers that successfully formed pods were positively correlated with increased yield. Keywords: Goat Waste Bokashi, Pests, Mung Beans